Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1039/c001779e
|View full text |Cite
|
Sign up to set email alerts
|

Structure determination of adsorbed hydrogen on a real catalyst

Abstract: Here we show that neutron diffraction can experimentally measure distances involving hydrogen on real catalysts. This method is applicable to adsorbed hydrogen (and other hydrogenous species) on crystalline, nanocrystalline or amorphous materials, supported and unsupported metals as well as oxides and works at ambient temperature and pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…Such information is of upmost importance fort he computational description of reaction mechanisms. Although neutrons cattering has been extensively used to study the interactions of hydrogen-containing speciesw ithb ulk metallic materials, such as Raney nickel,R aney palladium, palladium black, and platinum black, [15][16][17][18][19] many catalysts of practical interest consist of an activem etal (typically an oblem etal) depositedo nas upport. These supported-metal catalysts aim to expose as many active sites as possible;t hus reducing the cost of the catalyst.…”
Section: Hydrogen Adsorption and Spillovermentioning
confidence: 99%
“…Such information is of upmost importance fort he computational description of reaction mechanisms. Although neutrons cattering has been extensively used to study the interactions of hydrogen-containing speciesw ithb ulk metallic materials, such as Raney nickel,R aney palladium, palladium black, and platinum black, [15][16][17][18][19] many catalysts of practical interest consist of an activem etal (typically an oblem etal) depositedo nas upport. These supported-metal catalysts aim to expose as many active sites as possible;t hus reducing the cost of the catalyst.…”
Section: Hydrogen Adsorption and Spillovermentioning
confidence: 99%
“…Neutron News gen covered surface as shown by INS spectroscopy [5], Figure 3 (solid line). The spectrum is similar to that obtained earlier by other investigators, although more structure is evident because of the better resolution of TOSCA at ISIS as compared to the instruments used previously.…”
Section: Scientifi C Reviewsmentioning
confidence: 98%
“…No ordinate scaling has been applied; all the distances come directly from the ab initio calculation. Reproduced from [5] with permission from the Royal Society of Chemistry.…”
Section: Scientifi C Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that it is possible to obtain structural information about adsorbates on real catalysts at ambient temperature and pressure by total scattering neutron diffraction [10]. The aim of this paper was to obtain a structural characterization of formate bonded to a real catalyst surface by chemisorption of formic acid on Raney TM Cu.…”
Section: Introductionmentioning
confidence: 99%